FURTHER DECOMPOSITIONS OF∗-CONTINUITY - O. Ravi; M. Suresh; A. Nalini Ramalatha (Journal of New Theory)
− In this paper, we introduce the notions of*g-I-LC*-sets, I**g-closed sets and I-*gt-sets.Also we define the notions of*g-I-LC*-continuous maps, I*g-continuous maps, I-*gt-continuous mapsand obtain decompositions of *-continuity